Cerebral Phaeohyphomycosis Caused by Exophiala dermatitidis in a Chinese CARD9-Deficient Patient: A Case Report and Literature Review - Wang, Chen; Xing, Hongyi; Jiang, Xiaobing; Zeng, Jingsi; Liu, Zhijun; Chen, Jixiang; Wu, Yan (Frontiers in Neurology, 2019)
Exophiala dermatitidis, a dematiaceous fungus, typically found in decaying organic matter worldwide, is a rare cause of fungal infections. Cerebral phaeohyphomycosis caused by Exophiala dermatitidis is an extraordinarily rare, but frequently fatal fungal infection of the brain. However, with sporadic reports, little is known about its specific predisposing factors, clinical manifestation, and optimal treatment modality. Here, we report a clinical presentation and management of cerebral phaeohyphomycosis caused by Exophiala dermatitidis in a Chinese patient. An otherwise healthy, young male who was diagnosed with neck fungal lymphadenitis caused by Exophiala dermatitidis seven months prior and was treated with itraconazole, presented later with progressive intracranial hypertension and persistent coma. Culture of the neck lymphoid tissue produced a growth of black yeast-like fungus, which was identified as Exophiala dermatitidis by sequencing of the ribosomal DNA internal transcribed spacer (ITS) domains. Accordingly, a cerebral biopsy was carried out, and the pathological report showed mycelia and fungal granulomas. We also sequenced CARD9 gene in the patient and found him to be homozygous for loss-of-function mutation; his parents were heterozygous for the same mutation. This is a first case report of cerebral phaeohyphomycosis caused by Exophiala dermatitidis in a CARD9-deficient patient from China. He eventually succumbed to brain herniation and severe lung infection with a poor response to therapy. Thus, previously healthy patients with unexplained invasive E. dermatitidis infection, at any age, should be tested for inherited CARD9 deficiency.